The Impact of Auctions on Residential Sale Prices : Australian Evidence - Alex Frino; Andrew Lepone; Vito Mollica; Anthony Vassallo (Australasian Accounting, Business and Finance Journal, 2010)
This study re-examines the variation in selling prices between the auction and private treaty method of sales. Using sales data from five major Australian capital cities over a four year period, we estimate a hedonic pricing model. Results indicate that for house sales, auctions lead to greater selling prices across all cities examined. However, results for unit sales reveal that this auction premium is only evident in two cities where auctions are less prevalent. Further analysis reveals that self-selection (where a particular method of sale is selected to maximise the selling price) is evident across the sample. After controlling for this self-selection bias using a two-stage model, houses sold via auction generally command a higher price. This suggests that the auction method of selling provides a price premium over the private treaty method of sale.
Keywords: Residential real estate; Auctions; Private treaty